Progress and challenges of network meta‐analysis. Issue 3 (30th August 2021) - Tian, Jinhui; Gao, Ya; Zhang, Junhua; Yang, Zhirong; Dong, Shengjie; Zhang, Tiansong; Sun, Feng; Wu, Shanshan; Wu, Jiarui; Wang, Junfeng; Yao, Liang; Ge, Long; et al.
Abstract: In the past years, network meta‐analysis (NMA) has been widely used among clinicians, guideline makers, and health technology assessment agencies and has played an important role in clinical decision‐making and guideline development. To inform further development of NMAs, we conducted a bibliometric analysis to assess the current status of published NMA methodological studies, summarized the methodological progress of seven types of NMAs, and discussed the current challenges of NMAs.